2020
DOI: 10.2147/ahmt.s280800
|View full text |Cite
|
Sign up to set email alerts
|

<p>Thyme Tea and Primary Dysmenorrhea Among Young Female Students</p>

Abstract: Background: Thyme tea, locally known as "tossign tea", is one of the most popular herbaltea in Ethiopia used for the medicinal attribute, besides adding aroma and flavor to the tea. Therefore, this study aimed to assess the effect of thyme tea-drinking and other dietary factors of school girls on primary dysmenorrhea. Methods: An institutional case-control study was conducted from December 2019 to March 2020 in the suburbs of Debre Berhan town, Ethiopia. Data were collected through a face-to-face interview usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
1
4
1
1
Order By: Relevance
“…Oregano extract at 800 mg/kg induced an impressive 97.83% inhibition, surpassing that of tramadol. Similarly, thyme extract at 800 mg/kg achieved a significant 90.54% inhibition; these results corroborate earlier studies on oregano and thyme extracts, reaffirming their pronounced efficacy in alleviating pain [34][35][36][37][38].…”
Section: Analgesic Effect Of O Grosii and T Pallidus Total Extractssupporting
confidence: 88%
“…Oregano extract at 800 mg/kg induced an impressive 97.83% inhibition, surpassing that of tramadol. Similarly, thyme extract at 800 mg/kg achieved a significant 90.54% inhibition; these results corroborate earlier studies on oregano and thyme extracts, reaffirming their pronounced efficacy in alleviating pain [34][35][36][37][38].…”
Section: Analgesic Effect Of O Grosii and T Pallidus Total Extractssupporting
confidence: 88%
“…18 According to a study conducted in Ethiopia, 69.26% of participants there reported having dysmenorrhea, which supports the ndings of the current study. 19 Our study found no significant dierence in QOL between the groups with and without dysmenorrhea; the good QOL in the dysmenorrhea group was 59.4%, while the bad QOL was 71.4%. These ndings are almost identical to those of a study conducted in 2019 at a university in Spain.…”
Section: Discussioncontrasting
confidence: 67%
“…These ndings are almost identical to those of a study conducted in 2019 at a university in Spain. (19). Additionally, there was no noticeable dierence in the means between the two groups in the areas of physical, psychological, social, and environmental factors.…”
Section: Discussionmentioning
confidence: 82%
“…However, there was a statistically significant increase in severe dysmenorrhea among women who did not consume fruits. Zeru et al 16 in a case control study found that thyme tea-drinking, consumption of vegetables and fruits had a relieving effect while coffee drinking was positively associated with primary dysmenorrhea. In a study conducted in Kuwait involving a similar ethnicity to ours, Al-Matouq et al 17 found that there was a significant association between drinking coffee and dysmenorrhea.…”
Section: Discussionmentioning
confidence: 98%